2021
DOI: 10.1016/j.ymthe.2020.09.026
|View full text |Cite
|
Sign up to set email alerts
|

EVs Containing Host Restriction Factor IFITM3 Inhibited ZIKV Infection of Fetuses in Pregnant Mice through Trans-placenta Delivery

Abstract: Zika virus (ZIKV) infection can lead to neurological complications and fetal defects, and it has attracted global public health concerns. Effective treatment for ZIKV infection remains elusive, and a preventative vaccine is not yet available. Therapeutics for fetuses need to overcome placenta barriers to reach the fetuses and require higher safety standards. In the present study, we engineered mammalian extracellular vesicles (EVs) to deliver a host restriction factor, interferon-induced transmembrane protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…These EVs were also found to pass through the placental barrier and protect the fetus from ZIKV infection. These findings indicate that EVs containing IFITM3 can be used as treatment to minimize ZIKV infection during pregnancy [ 104 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…These EVs were also found to pass through the placental barrier and protect the fetus from ZIKV infection. These findings indicate that EVs containing IFITM3 can be used as treatment to minimize ZIKV infection during pregnancy [ 104 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…The distribution of sEVs RVG in mice was determined by an in vivo imaging system. 13 Figure 4A shows representative images of fluorescence distribution in pregnant mice after injection of sEVs. Tissues were dissected and image analysis revealed that nonengineered sEVs were mainly detected in the liver while RVG-modified sEVs concentrated more in the brain (Figure 4B).…”
Section: Optimization Of Loading Efficiency Of Sevs Rvg With Zikv-specific Sirnas and Inhibition Of Zikv Replication In Vitromentioning
confidence: 99%
“…Our previous study indicated that sEVs were able to deliver IFITM3, a placenta-bound antiviral molecule, across the placental barrier to inhibit ZIKV infection of mouse fetuses. 13 However, whether sEVs delivering antiviral drugs can achieve targeted suppression of ZIKV infection in the fetal CNS and control viral neurological damage of the fetuses remains to be elucidated. Rabies virus glycoprotein (RVG) specifically binds to the acetylcholine receptor expressed on the surface of neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The second step is poorly understood on a molecular level but may be explained by the localization of IFITM3 to late endosomes (also known as multivesicular bodies). IFITM3 is a constituent of intraluminal vesicles, and when they are released into the extracellular space as exosomes, provides antiviral protection to neighbouring cells 78 , 79 . Furthermore, it was reported that IFITM3 reduces the ‘back-fusion’ of intraluminal vesicles with the limiting membrane of the late endosome, thereby reducing the release of intraluminal cargo into the cytoplasm 80 .…”
Section: Ifitm Proteinsmentioning
confidence: 99%